Perkembangan Konsep Regionalisme Kritis Kenneth Frampton (1985-2005) - Dimas Wihardyanto; . Sherlia (JURNAL ARSITEKTUR, 2011)
This paper outlines the development of Critical Regionalism Concept, introduced by Kenneth Frampton, whom a professor in history and architecture. His most influential achievement was a book titled "Toward A Critical Regionalism", that introduced critical regionalism theory/thought as a response of globalization and universalization impact. His thought was based on the worry of excessive impact of modernism and globalism, and political situation at that time, causing buildings of western classic architecture style replaced by modern architecture style as symbols of industrialism. Critical Regionalism theory tried to put back architecture and buildings to the context and the development of its surrounding, as an effort to strengthen local identity by seeing its potency and noticing every details in buildings. Now, this theory is widespread and developed by world architects. These architects succeed in making modern architecture more tactile and tectonic, creating creative and tectonic structures forms, which able to counter universalism in architecture by placing back technology as instrument in architecture